The regulatory approval of anamorelin for treatment of cachexia in patients with non‐small cell lung cancer, gastric cancer, pancreatic cancer, and colorectal cancer in Japan: facts and numbers. Issue 1 (31st December 2020) - Wakabayashi, Hidetaka; Arai, Hidenori; Inui, Akio
Abstract: Anamorelin is a ghrelin receptor agonist that can be administered orally and thought to improve cancer cachexia by improving appetite and increasing serum insulin‐like growth factor‐1. Anamorelin was not approved for use in Europe. In contrast, the use of anamorelin for cancer cachexia in four types of cancer (non‐small cell lung cancer, gastric cancer, pancreatic cancer, and colorectal cancer) was approved in Japan on 11 December 2020. Phase 2 trial (ONO‐7643‐04) for the treatment of patients with non‐small cell lung cancer and cachexia resulted in 1.56 kg lean body mass increase assessed by dual‐energy X‐ray absorptiometry (DXA). Another study for advanced and unresectable gastrointestinal (colorectal, gastric, or pancreatic) cancer showed 1.89 ± 0.36 kg improvement in lean body mass. Skeletal lean body mass assessed by DXA is important for diagnosing sarcopenia and cachexia in Asia. The approval of anamorelin is expected to change clinical practice of cancer cachexia in Japan and hopefully in other countries. In the past, cachexia was rarely diagnosed in Japan, because it was often thought that cachexia meant terminal stage. The dissemination of clinical findings on anamorelin from Japan, as well as the creation of consensus papers and clinical practice guidelines for cachexia in Japan and Asia, will be required to promote international expansion in the future.